Representation of the Pancajiwa of Islamic Boarding Schools in the Film "Cahaya Cinta Pesantren" - Hidayat, Rahmat; Sukarno, Sukarno; Hadi, Sofyan; Ahmadi, Ahmadi (MUHARRIK: Jurnal Dakwah dan Sosial, 2022)
This article represents the pancajiwa (five souls) of Islamic boarding schools in the film "Cahaya Cinta Pesantren" using Charles Sanders Peirce's semiotic techniques, Peirce's triadic model, often also called Peirce's triangular theory of meaning, which consists of signs, objects, and interpretants. This article uses qualitative and semiotic methods, as well as document study. The purpose of this article is to represent the pancajiwa (five souls) of Islamic boarding schools in the film "Cahaya Cinta Pesantren". The results of this research show that the film "Cahaya Cinta Pesantren" contains the five souls of Islamic boarding schools in the form of the spirit of sincerity, namely sincerity in terms of giving because of God Allah, seeking knowledge and being warned, the spirit of simplicity in clothing, places to study, worship and to eat, the spirit of independence, namely independence in self-actualization and daily activities, the spirit of Ukhuwah Islamiyah namely brotherhood in overcoming problems without prioritizing individual egos and prioritizing togetherness and happiness of other people, the spirit of freedom, namely freedom of expression and work.